Metabotropic glutamate and dopamine receptors co-regulate AMPA receptor activity through PKA in cultured chick retinal neurones: effect on GluR4 phosphorylation and surface expression - Gomes, André R. (2004)
Glutamate receptor phosphorylation has been implicated in several forms of modulation of synaptic transmission. It has been reported that protein kinase A (PKA) can phosphorylate the 03B1-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptor subunit GluR4 on Ser842, both in vitro and in vivo. Here, we studied the regulation of GluR4 phosphorylation and intracellular trafficking by PKA and by metabotropic receptors coupled to adenylyl cyclase (AC), in cultured chick retinal amacrine-like neurones, which are enriched in GluR4. The regulation of AMPA receptor activity by PKA and by metabotropic AC-coupled receptors was also investigated by measuring the [Ca2+]i response to kainate in Na+-free medium. Stimulation of AC with forskolin (FSK), or using the selective agonist of dopamine D1 receptors (±)-1-phenyl-2,3,4,5-tetrahydro-(1H)-3-benzazepine-7,8-diol (SKF38393), increased the [Ca2+]i response to kainate, GluR4 phosphorylation at Ser842 and GluR4 surface expression. Pre-incubation of the cells with (2S,2'R,3'R)-2-(2',3'-dicarboxycyclopropyl)glycine (DCG-IV), an agonist of group II metabotropic glutamate receptors (mGluR), which are coupled to inhibition of AC, inhibited the effect of FSK and of SKF38393 on AMPA receptor activity, GluR4 phosphorylation and expression at the plasma membrane. These results indicate that there is a functional cross-talk between dopamine D1 receptors and group II mGluR in the regulation of GluR4 phosphorylation and AMPA receptor activity. Our data show that GluR4 phosphorylation at Ser842 by PKA, and its recruitment to the plasma membrane upon phosphorylation, is regulated by metabotropic receptors.